Developing a Digital Flipbook for IPAS Learning to Enhance Students’ Scientific Literacy - Amran, Muhammad; Umar, Indah Inriani; Lukman; Sahabuddin, Erma Suryani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
The rapid integration of digital technologies into elementary education necessitates the development of interactive learning media that are pedagogically grounded, curriculum-aligned, and accessible. This study aimed to develop a digital flipbook for Natural and Social Sciences (IPAS) learning, designed to support the enhancement of scientific literacy among fourth-grade elementary school students. Despite growing scholarly attention to digital flipbooks, a critical gap persists in the literature regarding the development of curriculum-based interactive flipbooks that explicitly integrate scientific literacy indicators, multimedia content, and QR-code accessibility for IPAS learning at the elementary level. This study employed a Research and Development (R&D) design following three stages of the ADDIE model: analysis, design, and development. Data were collected through classroom observations, semi-structured teacher interviews, expert validation sheets, and practicality questionnaires administered to teachers and students. Both qualitative and quantitative data were analyzed descriptively. The developed digital flipbook encompasses learning materials, instructional videos, interactive games, QR codes, and structured evaluation activities. Expert validation yielded highly favorable results, with scores of 91.2% for media aspects and 87.5% for content aspects, both categorized as very feasible. Practicality testing produced scores of 97.7% from teachers and 99.7% from students, likewise classified as very feasible. These findings confirm that the digital flipbook is valid, practical, accessible, and contextually appropriate for supporting IPAS learning and scientific literacy among elementary school students. The study provides a replicable model for the development of contextual, interactive, and curriculum-aligned digital learning media within the Merdeka Curriculum framework.